Petrus Hispanus O. P.,Auctor Summularum (II): nuevos documentos y problemas - D’ors, Ángel (Dicenda. Estudios de lengua y literatura españolas, 2008)
This article follows up on the investigation of the identity of «Petrus Hispanus», the «auctor Summularum», which I set off in my work «Petrus Hispanus O. P., Auctor Summularum» (1997). In this earlier paper I maintained, against what was then the unanimously established opinion, that the «auctor Summularum» could not be identified as Pope John XXI and must instead have been a Spanish Dominican. In the present paper I respond to some of S. Tugwell’s objections (published in 1999) to some of the hypotheses which I put forward in my earlier article, and I also follow up the analysis of the commentaries to the Divine Comedy, the histories of the Order of Friars Preachers, of Spanish authors, of the Pontiffs and of Lusitanian authors, as well as studying the manuscripts and editions of the Tractatus, which have yielded new evidence supporting my earlier theses. I also solve some specific problems as to the identities of «Petrus Hispanus recentior» and «Petrus Alfonsi», and I explore other literary traditions connected to the political history of Castille and Leon during the first third of the 13th century, as well as to the Cantigas of King Alfonso X and the history of the University of Palencia and of the convent of Santa María de la Mascarella in Bologne, aiming to find new evidence which may shed light on the life of «Petrus Hispanus O. P.», the «auctor Summularum».